Socio-Economic Factors Influencing the Adoption of Integrated Crop Management Technology in Rice For Sustainable Agribusiness Development - Tintin Febrianti; Fitri Rahmawati; Mukhlis Mukhlis; Dadan Suryana (Postgraduate, University of Mataram, 2024)
Adoption of Integrated Crop Management technology of rice is considered to increase production and income, also expected to be environmentally friendly. The purpose of this study was to determine the level of application of IPM and analyze the influence of socio-economic factors of farmers on the adoption of IPM technology. This research method was a survey, data collection using structured interviews using a measuring scale that is ordinal. Sampling with simple random sampling technique, the samples number used as many as 30 rice farmers. The data analysis technique used multiple linear regression method using the SPSS. The results found that the level of adoption of rice PTT technology in three subsystems: subsystem of supplying production facilities, cultivation subsystem, and post-harvest subsystem categorized as moderate. In adopting PTT rice, farmers have not fully considered the recommendations required by PTT rice. Simultaneously, age, education, land area, and length of farming together have a positive and significant effect. But partially that age, and length of farming have a positive and significant effect on rice PTT, while education and land area used do not have a positive and significant effect on the application of rice PTT in Putera Sejahtera Farmer Group